Uji Aktivitas Farmakologi Buah Jambu Biji (Psidium guajava L.) - Sepbrilla Ananda K; Mulia Maharani; Virgiawan Kusuma; Firlia Nur Afifah; Bella Fevi Aristia (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Guava (Psidium guajava L.) is a plant widely used in traditional medicine because it contains various bioactive compounds, such as flavonoids, phenolic compounds, tannins, alkaloids, terpenoids, lycopene, and vitamin C. These compounds are known to have various pharmacological activities that have the potential to support health. This opinion article aims to review and analyze the pharmacological activities of guava based on research results published in the period 2020–2025. The method used is a literature study of 11 national and international scientific journals selected according to the research topic. Data were analyzed descriptively by comparing findings regarding the biological activities of various plant parts, especially the fruit, fruit peel, and leaves. The results show that guava has various pharmacological activities, including antioxidant, antibacterial, antidiabetic, anticancer, anticholesterol, antimicrobial, and adaptogenic. Antioxidant activity is the most frequently reported effect, which is related to the high content of flavonoids, phenolic compounds, and vitamin C as free radical scavengers. Furthermore, several studies have shown that guava bioactive compounds can inhibit the activity of α-amylase and α-glucosidase enzymes, inhibit the growth of various pathogenic bacteria, and suppress the proliferation of cancer cells through various biological mechanisms. These findings indicate that guava has promising prospects for development as a raw material for herbal medicines and as a supportive therapy for various diseases. However, most of the available scientific evidence still comes from in vitro, in silico, and preclinical studies and therefore cannot be fully generalized to humans. Therefore, further research is needed, especially clinical trials with more comprehensive designs, to ensure the effectiveness, safety, optimal dosage, and potential use of guava in clinical practice.